Transformatorji: Učbenik - Ritonja, Jožef; Zagradišnik, Ivan (2020)
Transformers: Textbook.The textbook describes the presentation of an ideal and real single-phase transformer. The following is a presentation of single-phase, three-phase standard and special transformers. The final example shows the design of a small three-phase transformer.
Keywords: transformers; textbook; voltage transformers; current transformers; design